Impact of the green revolution on the gender’s role in wet rice farming: A case study in Karangwangi Village, Cianjur District, West Java, Indonesia - RUHYAT PARTASASMITA; BUDIAWATI S. ISKANDAR; SITI NURAENI; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2019)
Partasasmita R, Iskandar BS, Nuraeni S, Iskandar J. 2019. Impact of the green revolution on the gender’s role in wet rice farming: A case study in Karangwangi Village, Cianjur District, West Java, Indonesia. Biodiversitas 20: 23-36. The wet rice farming (sawah) is very complex that is determined by ecological and social economic and cultural factors, including soil conditions, water availability, weather and climate, population, local knowledge, beliefs, technology, and economy. In addition, wet rice farming is determined by the government policy and market economy. In the past, the Sundanese rural people of West Java practiced the wet rice farming based on the local knowledge or traditional ecological knowledge which is strongly embedded with local tradition, and division of labor based on the gender. Traditionally, most inputs of the wet rice farming, including rice seeds, organic fertilizer, and biopesticides were provided by internal resources of rural ecosystem. Both male and female farmers intensively involved in various t wet rice farming activities based on the gender which is embedded by local tradition. For example, female farmers involved work in various activities that do not need energy but need to be careful and diligent, including the selection of rice seeds. Conversely, some works, including hoeing and plowing, were undertaken by male farmers. In the late 1960s, the Indonesian government modernized the wet rice farming through the Green Revolution program. Consequently, most rural farmers of West Java adopted this program. This research aimed to elucidate the impact of the Green Revolution program on the wet rice farming activities of Karangwangi village, Cianjur, West Java based on the gender issue. Aqualitative method with an ethnoecological approach was used in this study, while some techniques including observation, participant observation, and semi-structured interview were applied in this research. Thestudy result shows that in the past the wet rice cultivation of Karangwangi was traditionally carried out based on the local knowledge and embedded with local cultures, including traditional beliefs. Various activities of each stage of the wet rice farming were undertaken by male and female farmers based on gender and strongly embed by local tradition. By introduction of the Green Revolution, the female farmers have still involved in various activities of the wet rice farming. However, some female activities, including observation of star in the sky, rice seed selection, and ponding of rice grains of post-harvesting have been lost due to the introduction of the Green Revolution.